Filter Air Bersih Bagi Warga Perumahan Arofatunna Kelurahan Karang Joang - Faisal Manta; Kholiq Deliasgarin Radyantho; Hadhimas Dwi Haryono (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The community service program, namely Health Water Filters for Subsidized Housing Residents, aims to provide solutions to the problem of clean water availability. The problem of clean water availability is generally faced by residents in remote areas, especially the Arofatunna subsidized housing, Jalan Batu Ratna, Karangjoang District, North Balikpapan. Community service activities were carried out on Saturday, November 10, 2018 at the home of one of the residents of the Arofatunna Housing. In this activity, counseling was provided on the importance of clean water and types of water filters. In addition, training was also carried out on making filters and how to install them. Filters made of beach sand, charcoal and gravel are used because they have the ability to filter and purify water and are economical. The filter installation uses PVC pipes and plastic drums because they are easy to obtain, economical and safe for the community. Residents were given detailed training on making water filters starting from the tools and materials needed to how to use and maintain water filters. At the end of the activity, free filters were distributed to residents who took part in the training. Based on the questionnaire results, it was found that 60% of participants knew the importance and impact of clean water on health, 70% of participants understood and were able to make water filters independently and 80% believed that the water filter improved water quality such as reducing turbidity and odor.